Joint single cell DNA-seq and RNA-seq of gastric cancer cell lines reveals rules of in vitro evolution. Issue 2 (14th March 2020) - Andor, Noemi; Lau, Billy T; Catalanotti, Claudia; Sathe, Anuja; Kubit, Matthew; Chen, Jiamin; Blaj, Cristina; Cherry, Athena; Bangs, Charles D; Grimes, Susan M; Suarez, Carlos J; Ji, Hanlee P
Abstract: Cancer cell lines are not homogeneous nor are they static in their genetic state and biological properties. Genetic, transcriptional and phenotypic diversity within cell lines contributes to the lack of experimental reproducibility frequently observed in tissue-culture-based studies. While cancer cell line heterogeneity has been generally recognized, there are no studies which quantify the number of clones that coexist within cell lines and their distinguishing characteristics. We used a single-cell DNA sequencing approach to characterize the cellular diversity within nine gastric cancer cell lines and integrated this information with single-cell RNA sequencing. Overall, we sequenced the genomes of 8824 cells, identifying between 2 and 12 clones per cell line. Using the transcriptomes of more than 28 000 single cells from the same cell lines, we independently corroborated 88% of the clonal structure determined from single cell DNA analysis. For one of these cell lines, we identified cell surface markers that distinguished two subpopulations and used flow cytometry to sort these two clones. We identified substantial proportions of replicating cells in each cell line, assigned these cells to subclones detected among the G0/G1 population and used the proportion of replicating cells per subclone as a surrogate of each subclone's growth rate.